2014
DOI: 10.1038/ng.3035
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ZBTB20 cause Primrose syndrome

Abstract: Primrose syndrome and 3q13.31 microdeletion syndrome are clinically related disorders characterized by tall stature, macrocephaly, intellectual disability, disturbed behavior and unusual facial features, with diabetes, deafness, progressive muscle wasting and ectopic calcifications specifically occurring in the former. We report that missense mutations in ZBTB20, residing within the 3q13.31 microdeletion syndrome critical region, underlie Primrose syndrome. This finding establishes a genetic link between these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 36 publications
4
117
0
Order By: Relevance
“…org/gatk/guide/best-practices). Called variants were filtered as previously reported (Cordeddu et al 2014;Niceta et al 2015;Kortum et al 2015). The predicted functional effect of variants was annotated with SnpEff toolbox V.4.…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…org/gatk/guide/best-practices). Called variants were filtered as previously reported (Cordeddu et al 2014;Niceta et al 2015;Kortum et al 2015). The predicted functional effect of variants was annotated with SnpEff toolbox V.4.…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…The mutation site of the ZBTB20 gene is conservative in all cases of Primrose syndrome, and the mutant amino acid residues are located in the first, second zinc finger region and the junction area of the zinc finger. In vitro experiments showed that the mutation of these loci reduced the binding ability of ZBTB20 protein to the target DNA fragments, and its ability of transcriptional inhibition was significantly reduced [17]. This finding establishes a genetic link between these disorders and delineates the impact of ZBTB20 dysregulation on brain development, cognitive function, growth and metabolism.…”
Section: Mental Illness With Znfsmentioning
confidence: 71%
“…ZBTB20 belongs to a family of transcription factors with an N-terminal BTB/POZ domain involved in protein-protein interaction and five C2H2 zinc fingers at the C terminus ( Figure 1), mediating protein binding to DNA [17]. ZBTB20 is expressed in developing neocortex and adult hippocampus.…”
Section: Mental Illness With Znfsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI may show basal ganglia calcifications. The condition is caused by ZBTB20 mutations [Cordeddu et al, 2014;Mattioli et al, 2016].…”
Section: Primrose Syndromementioning
confidence: 99%